Efficacy and late complications of laparoscopic pyeloplasty: Experience involving 125 consecutive ureters. Issue 2 (3rd December 2012) - Iwamura, Masatsugu; Nishi, Morihiro; Soh, Shigehiro; Ikeda, Masaomi; Matsumoto, Kazumasa; Fujita, Tetsuo; Baba, Shiro
Abstract Introduction Laparoscopic pyeloplasty is now widely recognized as a minimally invasive alternative for the surgical management of ureteropelvic junction obstruction. However, there have been insufficient reports describing the long‐term outcomes and the stability of the results. In addition, late complications have not been thoroughly discussed. Methods Between October 1999 and December 2010, we performed laparoscopic pyeloplasty on 125 consecutive ureters in 119 patients with an obstruction of the ureteropelvic junction. We performed dismembered Anderson‐Hynes pyeloplasty, Fenger plasty and Y‐V flap in 108 (86.4%), 15 (12.0%), and 2 ureters (1.6%), respectively. Results All procedures were completed successfully. Median operative time was 200 min (range, 80–775 min) and median estimated blood loss was 20 mL (range, 20–250 mL). Intraoperative and postoperative complications categorized as Clavien grade II and III occurred in 11 (8.9%) procedures. Among them, three were observed after 12 months postoperative and all involved renal stones in the collapsed pelvis. In 120 (96%) ureters, hydronephrosis improved and/or obstructive pattern on diuretic renography disappeared during a median follow‐up period of 45 months (range, 5–146 months). The degree of hydronephrosis steadily improved for more than 2 years, and re‐obstruction was never observed after 1 year postoperative. Conclusion The efficacy of laparoscopic pyeloplasty seems to be durable over 2 years postoperatively. Because obstruction recurrence was not observed after 12 months postoperative, patients with complete disappearance of hydronephrosis may unnecessarily be followed longer than 2 years. However, cases with persisting hydronephrosis should be regularly monitored because of the remaining possibility of stone formation.